2009
DOI: 10.2165/11530030-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and Functional Impairment

Abstract: Migraine is a leading cause of disability worldwide; approximately half of those affected have such severe attacks that they cannot function normally in routine daily activities. Research is beginning to focus upon the burden of migraine between attacks, referred to as interictal burden. This burden encompasses worry and expectation of future attacks that consequently may be associated with limitations in social and family interactions, as well as work capacity. This review aims to increase physician awareness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 40 publications
(49 reference statements)
3
27
0
1
Order By: Relevance
“…These values have been systematically reported in several countries 1 , including Brazil 2 , thus highlighting the need for efficient approaches towards this condition. Migraine has a significant impact on the quality of life 3 , on health resources 4 , and on patients' professional and personal activities 5 .…”
mentioning
confidence: 99%
“…These values have been systematically reported in several countries 1 , including Brazil 2 , thus highlighting the need for efficient approaches towards this condition. Migraine has a significant impact on the quality of life 3 , on health resources 4 , and on patients' professional and personal activities 5 .…”
mentioning
confidence: 99%
“…It has been found that nearly half the world's population has an active headache disorder and according to the American Migraine Prevalence and Prevention study of 2004 (Lipton et al, 2007), migraine in particular has a prevalence of 12% in the general population, 18% in women, and 6% in men (Robbins and Lipton, 2010). Migraine is reported to be among the top 20 causes of disability worldwide, as more than half of those affected have such severe symptoms that they cannot function normally in their routine daily activities, including work, school, and social activities (Brandes, 2009). 48.2% of migraineurs reported some level of impairment, 22.1% were severely disabled, and more than half reported the need for bed rest (Lipton et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…48.2% of migraineurs reported some level of impairment, 22.1% were severely disabled, and more than half reported the need for bed rest (Lipton et al, 2007). In addition, during the periods between attacks, worry, stress, and expectation of future attacks may also lead to functional impairment, a phenomenon known as the interictal burden (Brandes, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Even when it is accurately diagnosed, health care professionals may not identify the levels and dimensions of functional impairment imposed by migraine. 14,15 Migraine is not immediately life-threatening, there is generally no objective physical disability, and the person may appear well between attacks. Migraine is comorbid with psychiatric disorders (e.g., depression and anxiety 16 ), cardiovascular disease (e.g., angina and myocardial infarction 17 ), metabolic syndromes (e.g., obesity 18 ), other neurologic disorders (e.g., epilepsy 19 and sleep disorders 20 ), and gastrointestinal disorders (e.g., irritable bowel syndrome 21 ) and lacks a specific disease biomarker.…”
mentioning
confidence: 99%